Synthesis of Novel 1,3,4-Oxadiazole-Derived α-Aminophosphonates/α-Aminophosphonic Acids and Evaluation of Their In Vitro Antiviral Activity against the Avian Coronavirus Infectious Bronchitis Virus - Shaima Hkiri; Marwa Mekni-Toujani; Elvan Üstün; Karim Hosni; Abdeljelil Ghram; Soufiane Touil; Ali Samarat; David Sémeril (MDPI AG, 2022)
An efficient and simple approach has been developed for the synthesis of eight dialkyl/aryl[(5-phenyl-1,3,4-oxadiazol-2-ylamino)(aryl)methyl]phosphonates through the Pudovik-type reaction of dialkyl/arylphosphite with imines, obtained from 5-phenyl-1,3,4-oxadiazol-2-amine and aromatic aldehydes, under microwave irradiation. Five of them were hydrolyzed to lead to the corresponding phosphonic acids. Selected synthesized compounds were screened for their in vitro antiviral activity against the avian bronchitis virus (IBV). In the MTT cytotoxicity assay, the dose-response curve showed that all test compounds were safe in the range concentration of 540-1599 µM. The direct contact of novel synthesized compounds with IBV showed that the diethyl[(5-phenyl-1,3,4-oxadiazol-2-ylamino)(4-trifluoromethoxyphenyl)methyl]phosphonate (5f) (at 33 µM) and the [(5-phenyl-1,3,4-oxadiazol-2-ylamino)(4-trifluoromethylphenyl)methyl] phosphonic acid (6a) (at 1.23 µM) strongly inhibited the IBV infectivity, indicating their high virucidal activity. However, virus titers from IBV-infected Vero cells remained unchanged in response to treatment with the lowest non-cytotoxic concentrations of synthesized compounds suggesting their incapacity to inhibit the virus replication inside the host cell. Lack of antiviral activity might presumably be ascribed to their polarity that hampers their diffusion across the lipophilic cytoplasmic membrane. Therefore, the interactions of 5f and 6a were analyzed against the main coronavirus protease, papain-like protease, and nucleocapsid protein by molecular docking methods. Nevertheless, the novel 1,3,4-oxadiazole-based α-aminophosphonic acids and α-amino-phosphonates hold potential for developing new hygienic virucidal products for domestic, chemical, and medical uses.